COMPETITION BETWEEN ROME AND CARTHAGE - Kholmurodov Otabek Murod ugli (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2020)
This article explores the theoretical foundations of competition between Rome and Carthage. Based on the results of the analysis, proposals and recommendations aimed at increasing both Carthage and Rome pursued aggressive foreign policy.